Modulação da resposta das ectonucleotidases em ratos infectados com Trypanosoma evansi através do uso de curcumina como pré-tratamento - Pereira, Andreia Bugnotto (2014)
Trypanosoma evansi is a protozoan parasite which infects a wide variety of mammalian hosts leading to the development of trypanosomiasis. Several papers have investigated the enzymatic changes in lymphocytes, important cells involved in immune responses, which are important for understanding the pathological mechanism of trypanosomiasis in animals. Among them we highlight the ectoATPases, enzymes that hydrolyze extracellular nucleotides and nucleosides of adenine. The curcumin (cur) has been associated with several beneficial effects associated with its use in animals experimentally infected with T. evansi, since this compound exhibits its properties among inflammatory and anti-parasitic effects. This study aimed to evaluate the activity of enzymes of the purinergic system in lymphocytes of rats supplemented or not with curcumin 30 days before infection with Trypanosoma evansi. Thirty-two adult male Wistar rats were divided into four groups. The uninfected control group (C) received saline intraperitoneally (IP), the infected control group (CI) received by the same route 0.2 ml of blood with 1x106 parasites and treatment with corn oil. The group pre-infection 20 (PreI20) received 20mg/kg curcumin and pre-infection group 60 (PreI60) received 60mg/kg of curcumin for 30 days prior to inoculation with T. evansi. After inoculation, the 03 treated groups continued to receive daily curcumin within 15 days before euthanasia. The NTPDase activity for both the hydrolysis of ATP to ADP increased significantly in the infected control group compared to the control group (P <0.05). The ADA activity decreased significantly in the infected control group compared to the control (P <.05). The use of curcumin at doses of 20 and 60 mg / kg for 30 days prior to infection with T.evansi reduced significantly NTPDase activity and increased significantly ADA activity in the treated groups (P <0.05). The results of this study support the evidence that the use of curcumin prior infection with T. evansi induces immunomodulatory effects, since they maintain the NTPDase activity reduced in lymphocytes, and maintains high ADA activity, favoring the response against the parasite. Thus, it is suggested that curcumin can be used as a food supplement for animals in areas where trypanosomosis is endemic.